Peran Kader Kesehatan Dalam Peningkatan Kesehatan Lanjut Usia (Lansia): The Role of Health Careers in Increasing Health Elderly (Elderly) - Charis Christiani; Agus Bahrudin; R Permadi Mulajaya (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
The increase in the number of elderly population (elderly) in the city of Semarang, the increase in the elderly will bring problems due to the aging process which causes a risk of decreasing health status. The elderly will become the strength of a country if they are in a healthy, independent, active and productive condition. One solution to achieve this requires the optimal role of health cadres. As a religious institution, GKJ Jatingaleh Semarang has a service task, one of which is health care for the elderly. To support this service, the PPM FISIP UNTAG Semarang Team conducted PPM activities at the church. The purpose of the PPM activities is assisting in the formation of health cadres; provide medical examination services and provide medical equipment needed in examination activities. The method used is mentoring and practice of health checks. The results of these activities were the formation of a GKJ Jatingaleh health cadre team with 5 cadres as members; health checks have been carried out on 47 elderly residents of GKJ Jatingaleh; and delivery of medical equipment.